Genetsko testiranje v športu - Kenig, Saša (Šport (Ljubljana), 2017)
Human genome is among individuals 99.9 % identical, there are, however, important differences in the remaining part. Several companies offer analysis of these small differences - genetic polymorphisms, for different purposes. For athletes, genetic testing is available to identify individuals with undiagnosed cardiac disorders or stronger susceptibility to bone and ligament injuries or concussion. There are also tests where polymorphisms relevant for physical performance are analyzed, based on which personalized training could presumably be advised. These test, in particular, raise concern among scientists. Even though, there is in fact scientific evidence supporting associations of genetic polymorphisms with sports performance, predictive values of such analysis are minimal. In the present article recent advances in the field are summarized together with the relevant ethical concerns.
Keywords: concussion; genetic testing; gensko testiranje; injuries; performance; poškodbe; pretres možganov; sport; šport; športna zmogljivost